1998
DOI: 10.1021/bi982018g
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Control of the Amidotransferase Domain of Carbamoyl Phosphate Synthetase

Abstract: Carbamoyl phosphate synthetase catalyzes the hydrolysis of glutamine by the nucleophilic attack of an active site cysteine residue through a mechanism that requires the formation of a gamma-glutamyl thioester intermediate. The steady-state mole fraction of the thioester intermediate was determined to be 0.23 in the presence and absence of ATP and bicarbonate. The kinetics of formation and hydrolysis of the gamma-glutamyl thioester intermediate during CPS catalyzed hydrolysis of glutamine were determined. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…2 Scheme I summarizes the reactions catalyzed by the four enzymes. A comparison of the structural and kinetic results reveals that these enzymes frequently exhibit allosteric interactions that synchronize the reactions to prevent the build-up of excess intermediate (12)(13)(14)(15)(16).…”
Section: From the ‡Enzyme Structure And Function Section Laboratory mentioning
confidence: 99%
“…2 Scheme I summarizes the reactions catalyzed by the four enzymes. A comparison of the structural and kinetic results reveals that these enzymes frequently exhibit allosteric interactions that synchronize the reactions to prevent the build-up of excess intermediate (12)(13)(14)(15)(16).…”
Section: From the ‡Enzyme Structure And Function Section Laboratory mentioning
confidence: 99%
“…For example, binding of ATP and bicarbonate to the large subunit of E. coli carbamoyl phosphate synthetase large subunit stimulates the k cat for glutamine hydrolysis at a site about 45 Å removed in the small enzyme subunit (11). Likewise, binding of chorismate to the anthranilate synthase component I subunit stimulates glutamine hydrolysis by the component II subunit by more than 30-fold (12).…”
Section: Replacement Of Ilementioning
confidence: 99%
“…molecular tunnel for transport of ammonia and carbamate. In the case of carbamoyl phosphate synthetase, glutaminase activity is accelerated 1000-fold by bicarbonate phosphorylation at a site 45 Å away (3,4,11).…”
mentioning
confidence: 99%
“…Much of the catalytic power of a GAT domain involves protection of ammonia gas as a reactant (2)(3)(4)11). In this study, we identified two classes (I and III, involving amino acid substitutions at amino acids 111 and 112) of mutants in the glutaminase domain that inhibit synthetase activity, using either glutamine or ammonia as the amide donor.…”
mentioning
confidence: 99%